Solanum americanum: reservoir for Potato virus Y and Cucumber mosaic virus in sweet pepper crops - Moura,Monika Fecury (2014)
Weeds can act as important reservoirs for viruses. Solanum americanum (Black nightshade) is a common weed in Brazil and samples showing mosaic were collected from sweet pepper crops to verify the presence of viruses. One sample showed mixed infection between Cucumber mosaic virus (CMV) and Potato virus Y (PVY) and one sample showed simple infection by PVY. Both virus species were transmitted by plant extract and caused mosaic in tomato (Solanum lycopersicum cv. Santa Clara), sweet pepper (Capsicum annuum cv. Magda), Nicotiana benthamiana and N. tabaccum TNN, and local lesions on Chenopodium quinoa, C. murale and C. amaranticolor. The coat protein sequences for CMV and PVY found in S. americanum are phylogenetically more related to isolates from tomato. We conclude that S. americanum can act as a reservoir for different viruses during and between sweet pepper crop seasons.